Meningkatkan Sikap Gotong Royong dengan Menggunakan Model Teams Games Tournament Siswa Kelas IV Sekolah Dasar Kristen 04 Salatiga - Laksita, Ayu; Wahyudi, Wahyudi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
From the results of the pre-cycle conducted in class IV of SD Kristen 04 Salatiga, it shows the problem that students tend to do activities individually when conducting group discussion activities and students who tend to be selective about friends when conducting group activities. The research activities were carried out with the aim of improving the character of mutual cooperation attitudes of students through the Teams Games Tournament model. The type of research used was Classroom Action Research (CAR). The researcher used the Kemmis and Mc. Taggart model which has 4 stages, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. The results of the study showed that the average observation of student character increased by 94% in the very good category. This percentage increased by 51% from cycle 1. Thus, from the research that has been carried out, it can be concluded that the use of the Teams Games Tournament model can improve the character of mutual cooperation attitudes.